Al-Qur’an sebagai Ruang Emansipasi Lansia: Reaktualisasi Nilai Ibadah dan Kemandirian dalam Program Pemberdayaan Masyarakat di Sekolah Lansia Salimah - Rochmah Nur Azizah (Islamic Education, 2025)
Older adults are often perceived as a passive and dependent group, whereas in the Qur’anic perspective every human being continues to possess the potential to perform good deeds, worship, and contribute throughout the life course. This study aims to analyze the reactualization of Qur’anic values as a foundation for the empowerment and emancipation of older adults through the Sekolah Lansia Salimah (SALSA) program. Using a qualitative descriptive approach with a field study method, data were collected through observation, in-depth interviews, and documentation of SALSA activities focusing on strengthening spirituality, mental health, and social–economic independence among older adults. The findings indicate that the internalization of Qur’anic values such as istiqamah (consistency), gratitude, righteous deeds, and ukhuwah (brotherhood) leads to observable changes in attitudes, increased self-confidence, greater independence, and heightened awareness among older adults to remain productive and empowered in later life. Old age is no longer perceived as a period of decline, but as a meaningful space for self-actualization and spiritual growth. This study offers an original contribution by demonstrating that a Qur’anic-based approach can function as an alternative, transformative, and context-sensitive paradigm for older adult empowerment within society.